Cleidocranial Dysplasia: Case Report of Three Siblings - Mathur, Rinku (Jaypee Brothers Medical Publishers, 2009)
Background: A family case report of cleidocranial dysplasia (CCD) with varied manifestations from father to three siblings is presented. CCD ( MIM # 119600) is a rare autosomal dominant skeletal dysplasia caused by CBAF1 gene ( OMIM 600211) with a wide range of variability. In all the cases generalized dysplasia in bone, prolonged retention of primary teeth and delayed eruption of permanent teeth were evident. Interestingly, there were no supernumerary teeth present. There was mandibular prognathism which was intercepted by occipital chin cup therapy. Aims and objective: To present the clinical manifestations, diagnostic imaging and treatment modalities along with dermatoglyphics in CCD patients. Conclusion: Cleidocranial dysplasia is an uncommon disorder however its clinical and radiological features are characteristic. In addition the CCD patients may be distinguished by specific dermatoglyphic markers. It carries with it several implications in terms of complications like skeletal malocclusion, dental caries, etc. Medical treatment is mainly directed at orthopedic and dental correction. A team approach to the management of dental abnormalities on a long-term basis with the overall goal to provide an esthetic facial appearance and functioning occlusion by late adolescence or early adulthood should be focused.